Cellphone banking and its impact on SADC transactional behaviour. - Kloeck, Michael (My University, 2014)
ABSTRACT Traditional banking i.e. visiting the branch to perform financial transactions is rapidly becoming outdated. The convergence of banking services with mobile technologies means that users are able to conduct banking services at any place and at any time through cellphone banking, overcoming consumer challenges relating to the way in which consumers receive their bank’s services (Gu, Lee, & Suh, 2009). Countries in Sub-Saharan Africa have a large unbanked or underbanked population, a market that could benefit from cellphone banking. The purpose of this research is to identify characteristics influencing the adoption of cellphone banking, and to analyse the impact cellphone banking has on customer’s transactional behaviour in the SADC region. A variety of ANOVA tests were conducted on an extract of data from one of the four major banks in South Africa which has a presence in South Africa, Namibia, Botswana, Lesotho, and Zambia to determine the influence various factors have on a customer’s transactional behaviour pre and post the adoption of cellphone banking and the change in transactional behaviour after the adoption of cellphone banking. The research showed that in the SADC region age, race, gender, marital status, income and internet banking are factors that significantly influence a customer’s transactional behaviour with respect to number of transactions and value per transaction before and after the adoption of cellphone banking. These results showed an overall significant increase in transaction volume from 4.34 to 5.86 transactions after the adoption of cellphone banking. Each country showed significant increases in transaction volume. The antithesis occurred in value per transaction. The customer’s value per transaction significantly decreased after the adoption of cellphone banking in South Africa, Botswana and Lesotho.
MBA 2013
Keywords: Banks and banking, Cell phones, Consumer behavior.